EVALUATION OF KNOWLEDGE ON THE DIAGNOSIS AND TREATMENT OF DENTIN HYPERSENSITIVITY BY DENTAL STUDENTS IN PARAÍBA (REMUNOM, 2024)
Dentin hypersensitivity is a condition in which the individual experiences painful symptoms after various stimuli on the tooth surface. The etiological factors, being related to biopsychosocial conditions, make the diagnosis complex, and there is a need to identify and differentiate it from other types of pathology. It is through the study of this condition that future dentists are trained to face the demands they will encounter when they graduate. If the diagnosis is accurate, the therapy can be applied successfully and the professional responsible can restore the patient's quality of life and well-being. This study assessed the level of knowledge of academics about the diagnosis and treatment of dentinal hypersensitivity. A cross-sectional observational study was carried out using the Google Forms tool and a questionnaire was answered by final year dental students from public universities in Paraíba, namely the Federal University of Campina Grande (UFCG), the Federal University of Paraíba (UFPB) and the State University of Paraíba (UEPB). As these were questions on questionnaires, this research was submitted to and approved by the Research Ethics Committee. The sample made up of 125 students showed statistically significant differences in all the questions addressed (gender, age, period of training and institution) to the detriment of the variables questioned during the survey on the management of DH. Students at public dental institutions in Paraíba feel safe and prepared for the diagnosis and treatment of Dentin Hypersensitivity, but have occasional doubts about the use of potassium nitrate and the timing of the use of desensitizers in treatment.